Fruit and vegetable consumption in relation to hepatocellular carcinoma in a multi-centre, European cohort study - Bamia, C (Br J Cancer, 2015)
BACKGROUND: Vegetable and/or fruit intakes in association with hepatocellular carcinoma (HCC) risk have been investigated in case–control studies conducted in specific European countries and cohort studies conducted in Asia, with inconclusive results. No multi-centre European cohort has investigated the indicated associations. METHODS: In 486 799 men/women from the European Prospective Investigation into Cancer and nutrition, we identified 201 HCC cases after 11 years median follow-up. We calculated adjusted hazard ratios (HRs) for HCC incidence for sex-specific quintiles and per 100 g d(−1) increments of vegetable/fruit intakes. RESULTS: Higher vegetable intake was associated with a statistically significant, monotonic reduction of HCC risk: HR (100 g d(−1) increment): 0.83; 95% CI: 0.71–0.98. This association was consistent in sensitivity analyses with no apparent heterogeneity across strata of HCC risk factors. Fruit intake was not associated with HCC incidence: HR (100 g d(−1) increment): 1.01; 95% CI: 0.92–1.11. CONCLUSIONS: Vegetable, but not fruit, intake is associated with lower HCC risk with no evidence for heterogeneity of this association in strata of important HCC risk factors. Mechanistic studies should clarify pathways underlying this association. Given that HCC prognosis is poor and that vegetables are practically universally accessible, our results may be important, especially for those at high risk for the disease.